The impact of sarcopenia on short‐term and long‐term mortality in patients with septic shock. Issue 4 (27th April 2022) - Oh, Hyung Jung; Kim, Jung Ho; Kim, Hye Rim; Ahn, Jin Young; Jeong, Su Jin; Ku, Nam Su; Choi, Jun Yong; Yeom, Joon‐Sup; Song, Young Goo
Abstract: Background: Despite medical advances, septic shock remains one of the main causes of high mortality in critically ill patients. Although sarcopenia is considered a predictor of mortality in septic shock patients, most studies have only investigated short‐term mortality, and those on long‐term prognosis are limited. We investigated the impact of sarcopenia on long‐term mortality in a large patient population with septic shock. Methods: A retrospective cohort study comprising 905 patients with septic shock was conducted from 2008 to 2019. Sarcopenia was defined based on the measurement of the total abdominal muscle area, assessed using abdominal computed tomography scans. Thereafter, we stratified the patients into two groups—sarcopenia and non‐sarcopenia groups—and compared the impact of sarcopenia on short‐term (28 days) and long‐term (1 year and overall) mortality using multivariable Cox proportional analysis. Results: A total of 905 patients were included, and the mean age was 65.7 ± 15.1 years. Among them, 430 (47.5%) patients were male and 407 (45.0%) had sarcopenia. We found that the 28 day, 1 year, and overall mortality rates in the sarcopenia group were significantly higher than those in the non‐sarcopenia group (13.8% vs. 6.4%, P < 0.001; 41.8% vs. 21.7%, P < 0.001; 62.2% vs. 35.7%, P < 0.001, respectively). Univariable Cox analysis showed that the sarcopenia group had a significant association with the increase in each mortalities compared with the non‐sarcopenia group (28 day mortality, hazard ratio (HR) = 2.230, 95% confidence interval (CI) [1.444–3.442], P < 0.001; 1 year mortality, HR = 2.189, 95% CI [1.720, 2.787], P < 0.001; overall mortality, HR = 2.254, 95% CI [1.859, 2.734], P < 0.001). Multivariable Cox analysis showed that both the short‐term and long‐term mortality rates remained significantly higher in the sarcopenia group than in the non‐sarcopenia group, even after adjusting for confounding variables (28 day mortality, HR = 2.116, 95% CI [1.312, 3.412], P = 0.002; 1 year mortality, HR = 1.679, 95% CI [1.291, 2.182], P < 0.001; overall mortality, HR = 1.704, 95% CI [1.381, 2.102], P < 0.001). Conclusions: Sarcopenia was associated with both short‐term and long‐term mortality in patients with septic shock. In clinical settings, close attention should be paid to these patients for both short‐term and long‐term outcomes.